EFFECTIVENESS OF MOTIVATIONAL INTERVIEWING AND SELF-EFFICACY TECHNIQUES IN FOSTERING HIV RISK-PROTECTIVE BEHAVIOUR AMONG MALE INMATES OF BORSTAL REMAND CENTRES IN NIGERIA (2014)
Adolescents in Borstal remand centres, even though in a highly restrictive environment are typically identified with risk-taking behaviours which increase their vulnerability to HIV infection with an attendant socio-economic impacts on the larger society. Hence, evidence has shown that the prevalence rate of HIV is higher among those in correctional settings than those in the larger society. However, previous studies have focused on the prevention, diagnosis and treatment of HIV among adolescents outside correctional settings with little attention on those in the remand centres, particularly in the Borstals. This study, therefore, investigated the effects of Motivational Interviewing (MI) and Self-Efficacy Techniques (SET) in fostering HIV risk-protective behaviour among male inmates of Borstal remand centres in Nigeria. It further examined the moderating influence of socio-economic status and age on responents. The study adopted a pretest-posttest control group experimental design with a 3x2x2 factorial matrix. Non- proportional random sampling technique was used to select 40 participants from each of the three Borstal remand centres located in Abeokuta, Ilorin and Kaduna totalling 120. The respondents‘ ages ranged between 13 and 20 with the mean age of 13.9. The two treatment groups were exposed to eight-week training in MI and SET while respondents in the control group received no psychotherapeutic training. Three instruments were used, namely, HIV Risk Behaviour Scale (r=0.86), Family and Environmental Sexual Risk Scale (r=0.78) and HIV Risk- Protective Behavioural Scale (r=0.71). Seven hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance. Motivational interviewing and Self-Efficacy had significant effects on HIV risk protective behaviour of the respondents (F(2,117) = 30.41 ױ2=.36);respondents in MI had the highest score in their HIV risk- protective behaviour ( ̅ = 38.84); followed by SET ( ̅ = 37.54) and those in control ( ̅=31.21).There was a significant moderating effect of socio-economic status on the respondents‘ HIV risk-protective behaviour (F(1,117) = 3.84 ױ2=.14) as respondents from high socio-economic background performed better ( ̅= 35.18) than those from low socio-economic background ( ̅= 34.00).The interaction effect of treatments and age was more significant on early adolescents respondents ( ̅=34.62) than with late adolescents ( ̅=34.45) and the interaction effect of adolescent age and socio-economic status was also significant ((F(1,117) = 4.54 ױ2=.41) However, there was no significant effect of adolescents‘ age on the HIV risk-protective behaviour of respondents as both early and late adolescents showed no significant difference in their HIV risk protective behaviour.The three way interaction effects of treatments, adolescents‘ age and socio-economic status was also not significant. Motivational interviewing and self-efficacy techniques were effective in fostering HIV risk-protective behaviour among adolescents in Borstal remand centres in Nigeria. The two approaches should, therefore be utilised by counselling psychologists among adolescents in remand centres. Also, more attention should be directed at late adolescents and those from low socio-economic background for better results in HIV risk- protective behaviour. Keywords: Male adolescent inmates, HIV risk-protective behaviour, Motivational interviewing, Self-efficacy techniques, Borstal remand centres. Word count: 488